2021
DOI: 10.1038/s41598-021-82420-z
|View full text |Cite
|
Sign up to set email alerts
|

Anaerococcus urinimassiliensis sp. nov., a new bacterium isolated from human urine

Abstract: To date there are thirteen species validly assigned to the genus Anaerococcus. Most of the species in this genus are anaerobic and of human origin. Anaerococcus urinimassiliensis sp. nov., strain Marseille-P2143T is member of family Peptoniphilaceae, which was isolated from the urine of a 17-year-old boy affected by autoimmune hepatitis and membranoproliferative glomerulonephritis using the culturomic approach. In the current study, a taxono-genomics method was employed to describe this new species. The strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…tRNA genes were predicted by tRNA SCAN SE, using the default option and all available sequence sources ( 40 ). Proteomes were predicted with BLASTp (E value of 0.001, minimum coverage and identity of 70% and 30%, respectively) against the Cluster of Orthologous Groups database ( 41 ). Antibiotic resistance genes were then predicted using the adapted strategy for CPR that was recently described in Maatouk et al ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…tRNA genes were predicted by tRNA SCAN SE, using the default option and all available sequence sources ( 40 ). Proteomes were predicted with BLASTp (E value of 0.001, minimum coverage and identity of 70% and 30%, respectively) against the Cluster of Orthologous Groups database ( 41 ). Antibiotic resistance genes were then predicted using the adapted strategy for CPR that was recently described in Maatouk et al ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the differences in the healthy group, several bacteria, which could be considered as candidates for beneficial microorganisms, were more commonly identified in healthy and less common in BE patients' nasal microbiomes, for instance, Corynebacterium accolens, Anaerococcus octavius, Anaerococcus urinomassiliensis, Peptoniphilus lacydonensis, Peptoniphilus grossensis and Snodgrassella alvi. Some of these bacteria are already known players of healthy microbiota and their protective properties have been previously described [47][48][49]. However, additional research into each of them should be carried out, since some of them also have been observed to exhibit pathogenic properties in certain situations [50,51].…”
Section: Discussionmentioning
confidence: 99%